Reviewing the Control of Meat pH and Light Scattering in Model Systems - Swatland, Howard J. (European Journal of Applied Sciences, 2025)
This review explains how a computer controlled system was developed to perfuse individual meat muscle fibres with phosphate buffer to change their pH. Fibres were mounted on a frame in an optical cell on a polarizing microscope to measure their birefringence. As pH was decreased, birefringence was increased. X-ray diffraction showed that this was caused by thick and thin myofilaments in the fibres moving closer together laterally. Small disks of intact muscle were measured in a macroscopic system to show that a decrease in pH caused an increase in reflectance. When pH was increased, reflectance decreased. These model systems explain how living muscle usually gets brighter as it becomes meat.